Caminhos do gênero no cárcere: um estudo sobre direitos humanos de mulheres trans e travestis na Penitenciária Professor Jason Soares Albergaria - Larissa Mascotte Carvalhaes (2024)
In recent years, it is possible to notice greater visibility in the public arena of specific populations in situations of deprivation of liberty, such as the LGBTQIA+ population. The commonly used discourse, that LGBTQIA+ people deprived of liberty are subject to a greater risk of human rights violations in these prison spaces, produces the narrative of the need for a safe and separate space for this group of the population. In this context, Resolution nº 173, of the State Secretariat of Justice and Public Security of the State of Minas Gerais, was published on July 21, 2021, which in addition to create a Reference Unit for the policy of holding the LGBTQIA+ population deprived of liberty, it listed a series of regulatory principles and rights that aim to protect this group of the population from the situation of absolute precariousness inherent to prison logic. Despite the idea of a specific prison for the LGBTQIA+ group bringing a status of efficiency and success in the face of the known failure of the Brazilian prison system, state regulations present problems and contain questionable provisions from the point of view of human rights, such as those that provide that Transgender people must be allocated to male or female cells according to the presence or absence of the biological organ that symbolizes the male: the phallus. It can be noted, therefore, that the supposed pioneering spirit of the State of Minas Gerais was linked to a biological model that uses pathologizing paradigms to condition the gender recognition of trans and transvestite people, in this case, gender reassignment surgery. In this context, the main questions that guided the research were: what are the changes implemented by SEJUSP Resolution nº 173 and how do they impact the human rights of trans and transvestite women in situations of deprivation of liberty? How do gender and sexuality relations permeate the State, public institutions and political practices in Minas Gerais? What role does the Law play in maintaining sexual and gender hierarchies? In this sense, starting from the need to reconstruct human rights, we align ourselves with the critical theory of human rights to maintain that the creation and implementation of human rights norms must overcome the symbolic normative plane, entering the political plane not only of elimination of discrimination and combating systemic inequalities, but also recognition of individual experiences that overcome the heterocisnormative paradigm. Therefore, even though inclusion measures aimed at this population group are important in combating discrimination and access to certain resources, SEJUSP Resolution nº 173 needs to be rethought, as the submission of a human right to the recognition of gender identity A medical intervention is based on an operation through which non-hegemonic experiences are understood from a pathologizing approach, legitimizing norms that hierarchize individuals between those who have or do not have the capacity to say about their own gender identity. On the other hand, it does not appear capable, by itself, of dismantling the institutional and structural dimensions of inequalities, as it does not reach the hierarchies and power dynamics that legitimize the exclusions and discriminations they seek to combat.